The Optimum Condition for Total Carotenoid Extraction from Orange Sweet Potato - Daimon Syukri; Rini Rini; Wellyalina Wellyalina; Jaswandi Jaswandi; Puja Nadia Sukma (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2023)
This study aimed to find the optimum conditions for extracting the carotenoid content in orange sweet potato in an applied application. The extracted carotenoids will be used as raw materials to produce rose-scented aromatic compounds (b-ionone). The extraction process was carried out on dry matter using maceration technique and using hexane as solvent. Other solvents such as methanol, ethanol, isopropanol and choloroform were also used to extract carotenoids from orange sweet potato. The use of wet samples and dry samples was also carried out in this study. The ratio of the solvent used with the material was 1:3. Based on the yield and spectrophotometric characterization, it was known that the extraction process with hexane solvent can extract carotenoid compounds from dry orange sweet potato powder if the extraction process is carried out 7 times